The Influence of Personal Factors, Interpersonal Factors, and Conspicuous Consumption on Consumers’ Purchase Intentions on Luxury Brand. - Wang, Xuheng (2019)
Dissertação de Mestrado em Marketing apresentada à Faculdade de Economia